2018
DOI: 10.1111/dmcn.13753
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life and peer relationships in adolescents with developmental coordination disorder and attention‐deficit–hyperactivity disorder

Abstract: HRQoL and peer relationships are negatively affected in adolescents with DCD and ADHD. WHAT THIS PAPER ADDS?: Children with developmental coordination disorder (DCD) do not display poorer overall health-related quality of life (HRQoL) versus typically developing controls. Having DCD and attention-deficit-hyperactivity disorder (ADHD) was associated with poorer HRQoL. Adolescents with DCD and ADHD experience significantly higher levels of peer victimization than typically developing adolescents. HRQoL and peer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 24 publications
0
48
0
5
Order By: Relevance
“…Once considered a disorder of childhood, there is increasing evidence that difficulties associated with DCD frequently persist into adolescence and beyond into adulthood (Blank et al, 2019). Research suggests that adolescents with DCD do less well academically than their peers (Harrowell et al, 2017) and are at risk of poor social and emotional outcomes (Dewey and Volkovinskaia, 2018;Piek et al, 2006;Skinner and Piek, 2001). An association between DCD and reduced physical fitness and health in adolescence has also been reported (Cantell et al, 2008;Coverdale et al, 2012;Wagner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once considered a disorder of childhood, there is increasing evidence that difficulties associated with DCD frequently persist into adolescence and beyond into adulthood (Blank et al, 2019). Research suggests that adolescents with DCD do less well academically than their peers (Harrowell et al, 2017) and are at risk of poor social and emotional outcomes (Dewey and Volkovinskaia, 2018;Piek et al, 2006;Skinner and Piek, 2001). An association between DCD and reduced physical fitness and health in adolescence has also been reported (Cantell et al, 2008;Coverdale et al, 2012;Wagner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative research exploring the experience of DCD in adolescence is limited and typically prioritises the perspective of parents (Missiuna et al, 2007;Stephenson and Chesson, 2008) or teachers (Missiuna et al, 2006), or reports adults' retrospective recollections (Fitzpatrick and Watkinson, 2003;Missiuna et al, 2008;Ruiz-Perez et al, 2018). Few studies have explored teenagers' contemporaneous experience of DCD (see for example Barnett et al, 2013;Dewey and Volkovinskaia, 2018;Lingam et al, 2014). The qualitative literature suggests two different trajectories for DCD in adolescence: while parents report increasing concerns for their child's social and emotional wellbeing in adolescence, studies in which people with DCD were the respondents are more positive.…”
Section: Introductionmentioning
confidence: 99%
“…25 The impact of motor impairments such as DCD on HRQoL is not well known. Dewey and Volkovinskaia 26 have found no differences in total HRQoL scores between adolescents with DCD and/or attention deficit hyperactivity disorder (ADHD) and typically developing adolescents. However, they found that adolescents with DCD and ADHD had lower HRQoL on the mood and emotions subscale and school environment subscale.…”
mentioning
confidence: 99%
“…Participants were referred by clinicians in the San Juan metropolitan area. Individual semistructured interviews (n=40) 3 focus groups (n=20) were conducted with a different cohort of participants (ie, not those who had been previously interviewed) Top 10 concepts for good QoL: 1) to feel able to accomplish goals; 2) to have a good attitude towards others; 3) to get good grades; 4) to respect others/not offend others; 5) to pay attention/concentrate at school; 6) to do things/participate in activities with others; 7) to behave well with others/not be rude; 8) to avoid looking for or getting in trouble; 9) to be healthy/to have good physical health; and 10) to not do things in a rush/to do them slowly Socialization=most prevalent focus group theme Being able to practice sports was most important for good QoL in interviews Believed not having a mental health condition would improve QoL N/A Dewey et al 15 To investigate HRQoL and peer relationships in adolescents with DCD and ADHD 44 adolescents in Canada (aged 11–18) recruited from a cohort study examining genetics and neurobiology of motor and attention problems ADHD only: n=9 DCD only: n=9 ADHD+DCD: n=10 Normally developing: n=19 Semistructured interviews exploring various aspects of HRQoL Most participants in ADHD-only group reported only enjoying nonsedentary activities (eg, playing sports, dancing, swimming) Close friends were a good source of support for all participants ADHD participants reported feeling alone, lonely, ignored, left out, or marginalized (as compared with typically developing peers) N/A Hareendran et al 16 To describe the experience of living with ADHD from the perspective of adolescents and their caregivers, for use in the creation of a new self-report instrument 3 teachers who had worked with students with ADHD 60 adolescents (aged 13–17) with a clinician- confirmed diagnosis of ADHD No other Axis I or II conditions (per DSM-IV) Stable off medication for 1 week (if stimulant)–4 weeks (if nonstimulant) or on medication for at least 4 weeks 60 primary caregivers (age 18+) of an adolescent with ADHD Individual interviews with teachers Individual interviews with adolescents Individual interviews with caregivers Interviews with adolescents and caregivers together (questions were addressed to adolescents first, then to caregivers to provide additional detail) Difficulties wit...…”
Section: Resultsmentioning
confidence: 99%